The (Trans)formation of Religious Capital in Indonesian Politics During New Order Era: A Case Study Of Nahdlatul Ulama - Muhammad R Damm (Journal of Indonesian Social Sciences and Humanities, 2018)
Religious capital always has crucial role in Indonesian politics. This paper aims to analyze the formation and transformation of religious capital in New Order era that has been heavily influenced by the dynamics of relationship between the state and religious groups, especially Islam, over time. As a case study, this paper will discuss Nahdlatul Ulama (NU). By analyzing the development of NU during the course of the New Order, it shows that the transformation can be divided in two phases. The first phase is the systematic weakening of Islamic movement since the late 1960s until the midst of 1980s. It is conducted by manipulation such as demonization of Islamic groups in 1960s, as well as by several policies and regulations such as simplification of political party system in 1973 and the enforcement of Pacasila as the sole principle for socio-political life in 1985. The second phase characterized by de-politicization of Islamic organizations since the midst of 1980s and at the same time, by capitalization of religious symbols and identity by individual politicians in political practices during 1990s.